2002
DOI: 10.2355/isijinternational.42.489
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cuspidine (3CaO 2SiO2 CaF2) and Phase Relations in the CaO-SiO2-CaF2 System.

Abstract: Primary crystallization field of cuspidine (3CaO · 2SiO 2 · CaF 2 ) has been experimentally determined in the 2CaO · SiO 2 -SiO 2 -CaF 2 system by quenching method and differential thermal analysis (DTA). Hermetically closed platinum capsules were used as a sample container to prevent fluorine loss in the form of HF and SiF 4 by reaction of CaF 2 with moisture or SiO 2 for quenching experiments. Combining the present study with the partial phase diagrams previously reported, the whole phase diagram of the CaO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 15 publications
(26 reference statements)
4
47
0
3
Order By: Relevance
“…If Li 2 O was substituted by Na 2 O, the following substitution reaction (1) should be taken into account according to Yasushi et al [31][32][33][34][35] But it was found that most of F Ϫ ions are fourfold coordinated by Ca 2ϩ rather than Na ϩ for samples of n Na /(n Na ϩn Ca )Յ0.3, and the presence of Na 2 O may not prevent the precipitation of cuspidine from the mold fluxes. [36][37][38][39] In the composition range of experimental samples, the value of n Na /(n Na ϩn Ca ) was less than 0.3, and it was confirmed by XRD that there was precipitation of cuspidine for all the samples. So Li 2 O substitution by Na 2 O has no effect on the crystal morphology in the crystalline film layer.…”
Section: The Results Of Xrd and Bsementioning
confidence: 81%
“…If Li 2 O was substituted by Na 2 O, the following substitution reaction (1) should be taken into account according to Yasushi et al [31][32][33][34][35] But it was found that most of F Ϫ ions are fourfold coordinated by Ca 2ϩ rather than Na ϩ for samples of n Na /(n Na ϩn Ca )Յ0.3, and the presence of Na 2 O may not prevent the precipitation of cuspidine from the mold fluxes. [36][37][38][39] In the composition range of experimental samples, the value of n Na /(n Na ϩn Ca ) was less than 0.3, and it was confirmed by XRD that there was precipitation of cuspidine for all the samples. So Li 2 O substitution by Na 2 O has no effect on the crystal morphology in the crystalline film layer.…”
Section: The Results Of Xrd and Bsementioning
confidence: 81%
“…Though thermo-dynamic data or phase diagram for cuspidine has begun to be reported recently, 6) it was not necessarily recognized as an important phase on metallurgy, and it does not exist on the phase diagram of CaO-SiO 2 -CaF 2 system. 7) Furthermore, the mold flux composition is difficult to be expressed accurately in the phase diagram because of its complication with many components, CaO, SiO 2 , Al 2 O 3 , MgO, Na 2 O, F, for examples.…”
Section: Introductionmentioning
confidence: 99%
“…CaF 2 ) is one of the most important crystallized compounds in mold flux film during thin slab casting process. Watanabe et al [10] , determined the primary crystallization field and the melting temperature of cuspidine. Differential thermal analysis have been carried out in order to determine the changes in thermal properties of mold flux [11 and 12] .…”
Section: Caracterización De Fundentes Para Molde De Planchón Delgado mentioning
confidence: 99%